2016
DOI: 10.1016/j.celrep.2016.05.019
|View full text |Cite
|
Sign up to set email alerts
|

LSD1 Interacts with Zfp516 to Promote UCP1 Transcription and Brown Fat Program

Abstract: SUMMARY Zfp516, a brown fat (BAT) enriched and cold-inducible transcription factor, promotes transcription of UCP1 and other BAT-enriched genes for non-shivering thermogenesis. Here, we identify lysine specific demethylase 1 (LSD1) as a direct binding partner of Zfp516. We show that, through interaction with Zfp516, LSD1 is recruited to UCP1 and other BAT-enriched genes, such as PGC1α, to function as a coactivator by demethylating H3K9. We also show that LSD1 is induced during brown adipogenesis and that LSD1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
81
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(81 citation statements)
references
References 28 publications
0
81
0
Order By: Relevance
“…While we were preparing this article, the same group published another paper suggesting that LSD1 is responsible for the H3K9 demethylation activity associated with ZFP516 (Sambeat et al 2016). They further showed that BAT-specific LSD1 knockout mice displayed an obese phenotype similar to what we observed with the AdLKO mice and suggested that the reduced UCP1 expression might be one of the underlying mechanisms.…”
Section: Discussionmentioning
confidence: 65%
“…While we were preparing this article, the same group published another paper suggesting that LSD1 is responsible for the H3K9 demethylation activity associated with ZFP516 (Sambeat et al 2016). They further showed that BAT-specific LSD1 knockout mice displayed an obese phenotype similar to what we observed with the AdLKO mice and suggested that the reduced UCP1 expression might be one of the underlying mechanisms.…”
Section: Discussionmentioning
confidence: 65%
“…Cold exposure stimulates expression of Zfp516 in BAT that binds to Prdm16 and stimulates UCP1 transcription (64, 267). In agreement with these findings, adipocyte-specific overexpression of Zfp516 increases brown adipogenesis in mice (64).…”
Section: Genetic and Epigenetic Regulation Of Brown And Beige Fat Thementioning
confidence: 99%
“…74 The HDAC inhibitor program of Novartis that led to the approval of panobinostat for the treatment of multiple myeloma, originated from a campaign that was looking for compounds that induce the overexpression of p21. 75 Several promoters have also been found to be regulated by LSD1, e.g., BAT gene promoters 76 or the mouse PGC-1a promoter. 78 The challenge with histone modifying enzyme is the incorporation of the transgene into the nucleosome.…”
Section: Reporter Gene Assaysmentioning
confidence: 99%